Esser bambini ai tempi di Collodi: attraverso Collodi - Franco Cambi (Firenze University Press, 2013)
The texts of Collody make an X-ray of the complexity of childhood in nineteenth century. Above all they point out the characteristics of the versions of popular childhood and bourgeois childhood.